2022
DOI: 10.3389/fimmu.2022.950001
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of a novel signature incorporating lipid metabolism and immune-related genes for assessing prognosis and immune landscape in lung adenocarcinoma

Abstract: BackgroundAs the crosstalk between metabolism and antitumor immunity continues to be unraveled, we aim to develop a prognostic gene signature that integrates lipid metabolism and immune features for patients with lung adenocarcinoma (LUAD).MethodsFirst, differentially expressed genes (DEGs) related to lipid metabolism in LUAD were detected, and subgroups of LUAD patients were identified via the unsupervised clustering method. Based on lipid metabolism and immune-related DEGs, variables were determined by the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A previous study reported that PSMC1 promotes the proliferation and migration of lung adenocarcinoma cells and is related to poor prognosis in patients with lung adenocarcinoma. 29 and metastasis of colorectal cancer and its high expression correlates with poor prognosis in colorectal cancer. 30 Consistent with studies in other tumor types, high expression levels of PSMCs correlated with poor prognosis and shorter survival in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that PSMC1 promotes the proliferation and migration of lung adenocarcinoma cells and is related to poor prognosis in patients with lung adenocarcinoma. 29 and metastasis of colorectal cancer and its high expression correlates with poor prognosis in colorectal cancer. 30 Consistent with studies in other tumor types, high expression levels of PSMCs correlated with poor prognosis and shorter survival in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Further comprehensive investigations are warranted to elucidate the precise underlying factors supporting this speculative interpretation Yang T et al found in vitro experiments that FLT3 expression was reduced in LIHC. They further analyzed its prognostic characteristics by plotting survival curves and found that the FLT3 high expression group had better survival outcomes than the low expression group [19] . Quizartinib is an inhibitor of FMS-like tyrosine kinase 3 (FLT3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have suggested that mast cells are an essential source of VEGF, which facilitates the proliferation and angiogenesis of tumors ( 47 , 48 ). Nevertheless, recent studies have characterized the heterogeneity of mast cells and proved that the subpopulation of CD103+ mast cells display a stronger expression of molecules associated with antigen presentation, which include CD80, ICAM-1 as well as MHC-II-like molecules, which effectively activate CD4+ T cells in turn ( 49 ). The proportion of CD4 memory resting T cell infiltration decreased significantly with increasing patient risk.…”
Section: Discussionmentioning
confidence: 99%